Understanding the Host Immune Response Against Mycobacterium tuberculosis Infection (Springer International Publishing, 2018)
According to the World Health Organization, approximately one third of the world's population is latently infected with Mycobacterium tuberculosis (M. tb [LTBI]), of whom about 9 million have active tuberculosis (TB). It is estimated that approximately 2 million individuals die each year from active TB. An estimated 14.4% of these individuals have HIV and M. tb co-infection. TB has long been known to be one of the leading causes of death in HIV-infected individuals. Recent evidence now indicates that individuals with type 2 diabetes, the elderly, and chronic smokers are also increasingly susceptible to TB infection, the ability of their immune system to fight off active TB infection having been compromised by their condition. This book therefore aims to provide a detailed review of recent advances in the research that involves characterizing the host's immune responses against TB infection in conditions such as HIV, diabetes, chronic cigarette smoking and aging, and strategies to restore favorable immune responses against this deadly pathogen.